LAGU NASIONAL SEBAGAI MEDIA PENANAMAN KARAKTER CINTA TANAH AIR PADA PESERTA DIDIK - Zamzami, Yuda; Rila Melyana Fitri; Diah Sunarsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The character of patriotism is an essential aspect of character education in elementary schools that needs to be instilled from an early age. However, observations at SD Negeri Rengaspendawa 03 show that most third-grade students do not yet fully recognize, memorize, or understand the meaning of national songs. This study aims to describe the process of instilling the character of patriotism through national songs and to identify the supporting factors in its implementation. This research employs a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results show that the character of patriotism is developed through routine singing of national songs, memorizing songs such as